System integration with slotting and ABC analysis - ÖZHAN DOĞAN, Serap; Ahmet KARATAŞ; Nihat BULDUK (International Journal of Computational and Experimental Science and Engineering, 2024)
Logistics companies operating in the service sector want to provide services to their customers for storing their ready-to-sell products (if the customer does not have their own warehouse) and manage the end-to-end supply chain in order to provide better service to their existing or new customers. They provide this service to their customers in their own warehouses and with their own systems in order to offer the supply, storage and shipping links together. Within the scope of this study, it was aimed to make a shelving plan so that the area of ​​an automotive spare parts warehouse that will provide this service can be used at the highest efficiency. After the designed shelf modeling area was put into use, ABC analyses and Slotting analyses were applied to increase its efficiency. As a result of the studies conducted; the efficiency increase in the goods acceptance and shipping processes was measured. It was determined that an average of 20% efficiency was achieved for goods acceptance, 25% efficiency for shipping and 30% efficiency was achieved for the efficient use of shelf capacity.